2001
DOI: 10.1097/00000658-200110000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Bile Duct Injury During Laparoscopic Cholecystectomy

Abstract: Accepting that the survey bias underestimates the true frequency of bile duct injuries, residency training decreases the likelihood of injuring a bile duct, but only by decreasing the frequency of early "learning curve" injuries. If one accepts a liberal definition of the learning curve (200 cases), it appears that at least one third of injuries are not related to inexperience but may reflect fundamental errors in the technique of laparoscopic cholecystectomy as practiced by a broad population of surgeons in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
230
1
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(247 citation statements)
references
References 36 publications
7
230
1
9
Order By: Relevance
“…Archer et al [13] reported that routine use of IOC increased detection of BDI from 45 % to 85 %, which is similar to the increased detection described by Ludwig et al [9] from 45 % to 90 %. Intraoperative detection of a ductal injury should decrease the technical difficulty of a repair, because there is no infection, inflammation, or fibrosis in the operating field compared with a delayed repair.…”
Section: Importance Of Intraoperative Detection Of Bdisupporting
confidence: 64%
See 2 more Smart Citations
“…Archer et al [13] reported that routine use of IOC increased detection of BDI from 45 % to 85 %, which is similar to the increased detection described by Ludwig et al [9] from 45 % to 90 %. Intraoperative detection of a ductal injury should decrease the technical difficulty of a repair, because there is no infection, inflammation, or fibrosis in the operating field compared with a delayed repair.…”
Section: Importance Of Intraoperative Detection Of Bdisupporting
confidence: 64%
“…Despite variation on opinions about the routine or selective use of IOC, it has demonstrated a reduction in the incidence of major BDI and expeditiously identifies insults at the time of surgery [2,13,52,59,[70][71][72][73]. Archer et al [13] reported that routine use of IOC increased detection of BDI from 45 % to 85 %, which is similar to the increased detection described by Ludwig et al [9] from 45 % to 90 %.…”
Section: Importance Of Intraoperative Detection Of Bdimentioning
confidence: 86%
See 1 more Smart Citation
“…Most complications occurred during the first 50 procedures which, despite the limitations of the report, suggest that most lesions are associated with inadequate expertise. Nevertheless, at least a third of those lesions might be associated with other factors such as those derived from inappropriate surgical maneuvers (Archer, 2001). A similar study with a 58% response rate observed 75.7% of major lesions, with no differences between the type of technique used or the use of RIOC (Nuzzo, 2005), (Treatment studies 4).…”
Section: Laparoscopic Cholecystectomy Related Bile Duct Injuriesmentioning
confidence: 88%
“…Approximately 30% of bile duct injuries are identified during the primary surgery. Optimal management of an IBDI depends on several factors, including type of injury, associated vascular injuries, condition of the patient, timing of reconstruction and availability of expertise, and includes open surgical and endo-therapeutic options [2]. Reconstructive hepaticojejunostomy which is commonly performed, is associated with low mortality and low morbidity [3,4].…”
Section: Introductionmentioning
confidence: 99%